2023
DOI: 10.1093/gerona/glad088
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Impact of a 10-Year Intensive Lifestyle Intervention on a Deficit Accumulation Frailty Index: Action for Health in Diabetes Trial

Abstract: Background Multidomain lifestyle interventions may slow aging as captured by deficit accumulation frailty indices; however, it is unknown whether benefits extend beyond intervention delivery. Methods We developed a deficit accumulation frailty index (FI-E) to span the ten years that the Action for Health in Diabetes (Look AHEAD) randomized controlled clinical trial delivered interventions (a multidomain lifestyle intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…These findings align those of Arakawa ( 45 ). In a study of an intervention trial conducted in a diabetic population with calorie restriction and increased physical activity and diet in the test group, the investigators found a relatively lower FI in the test group ( 46 ). Exercise has constructive impacts on nearly all body, particularly the skeletal system.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align those of Arakawa ( 45 ). In a study of an intervention trial conducted in a diabetic population with calorie restriction and increased physical activity and diet in the test group, the investigators found a relatively lower FI in the test group ( 46 ). Exercise has constructive impacts on nearly all body, particularly the skeletal system.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of BMI loss on FI may be larger than those for increased fitness, as seen in Figure 1 and Table 4; however, benefits for slowing the progression of FI associated with increased fitness were similar among those with BMI losses and BMI gains (based on the nonsignificant interactions). Across the full cohort, FI increased at a mean of about 0.01 units per year (37). Thus, the 4-yr differences seen in Figure 1, which range from about −0.02 to 0.03 units, may translate to 5-yr differences in “usual” aging in the Look AHEAD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting analyses will compare the prevalence, severity, and change in the following geriatric syndromes: depression, pain, vision impairment, hearing impairment, nutritional risk, urinary incontinence, falls, fractures, sleep, polypharmacy, and weight and unintentional weight loss. Look AHEAD Aging will also describe differences between ILI and DSE in a frailty index based on deficit accumulation, modeled after the indices previously developed in Look AHEAD 29,30 …”
Section: Look Ahead Aging Protocolmentioning
confidence: 99%
“…Look AHEAD Aging will also describe differences between ILI and DSE in a frailty index based on deficit accumulation, modeled after the indices previously developed in Look AHEAD. 29 , 30 …”
Section: Look Ahead Aging Protocolmentioning
confidence: 99%